2019
DOI: 10.1136/gutjnl-2018-316324
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-associated macrophages-derived CXCL8 determines immune evasion through autonomous PD-L1 expression in gastric cancer

Abstract: ObjectiveOur previous studies have identified CXCL8 as the crucial chemokine responsible for gastric cancer metastasis mediated by loss of RACK1. However, the regulatory effect of CXCL8 on immune surveillance in gastric cancer remains obscure.DesignFlow cytometry analyses were performed to examine major source of CXCL8 and phenotypes of immune cells in fresh tumour tissues from 76 patients with gastric cancer. Real-time PCR was performed to analyse CXCL8 mRNA level in gastric cancer tissues. For immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
215
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(220 citation statements)
references
References 32 publications
5
215
0
Order By: Relevance
“…Interruption of the related signaling pathways may thus provide promising therapeutic avenues for tumors. Studies have found that CXCL8 is predominantly secreted by macrophages and contributes to the immunosuppressive microenvironment by inducing PD-L1 + macrophages in GC [52]. CXCL8 inhibitors may drive antitumor response, providing potential therapeutic effects for patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Interruption of the related signaling pathways may thus provide promising therapeutic avenues for tumors. Studies have found that CXCL8 is predominantly secreted by macrophages and contributes to the immunosuppressive microenvironment by inducing PD-L1 + macrophages in GC [52]. CXCL8 inhibitors may drive antitumor response, providing potential therapeutic effects for patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 secreted by intraperitoneal TAMs promotes peritoneal dissemination of GC [163]. CXCL-8 present in the GC stroma is secreted mostly by macrophages, leading to an increased expression of PD-L1 on their surface [164]. This reduces CD8+ T-cells infiltration and impairs the anti-tumor immune response.…”
Section: Tumor-associated Macrophages In Gastric Cancermentioning
confidence: 99%
“…High CXCL8 secretion was associated with decreased CD8 + T cell infiltration, proliferation and function by inducing the expression of PD‐L1 on macrophages. The authors found that the small molecule CXR2 inhibitor (reparixin) drives the decreased PD‐L1 + macrophages and promotes antitumour immunity, providing potential therapeutic effects for GC patients 19 …”
Section: Immune Microenvironmentmentioning
confidence: 99%